Photoluminescent Carbon Dots for Sensitive and Selective Cu2+ Ion Detection - Sahin-Tiras, K.; Karabel Ocal, S.; Mutlugün, E.; Sahin Tiras, Kevser (Institute of Physics, 2026)
Green-emitting carbon dots (CDs) were synthesized via a solvent-free, vacuum-assisted method using citric acid and urea. The CDs exhibited strong photoluminescence and served as selective, sensitive probes for Cu2+ detection in water, with a detection limit of 26 nM. Among the tested metal ions, Cu2+ induced the most significant PL quenching. Time-resolved photoluminescence measurements of the CDs in the presence of Cu2+ ions revealed a minimal change in lifetime, despite a significant decrease in PL intensity, along with unchanged UV-vis absorption, indicating a mixed quenching mechanism. The sensor’s applicability was confirmed in raisin extract and tea infusion, showing notable PL suppression. With their simplicity, selectivity, and sensitivity, these CDs offer promising potential as nanosensors for detecting Cu2+ in environmental and real-world analytical settings. © 2026 The Author(s). Published by IOP Publishing Ltd.
Keywords: Carbon Dots; Cu2+ Detection; Dynamic Quenching; Pl Quenching; Real Sample Analysis; TRPL; Cu2+ Detection